Analysis and design of quantum secure communication system - Das, Nayana (Kolkata: Indian Statistical Institute, 2022)
Quantum secure direct communication (QSDC) is an important branch of quantum cryptog- raphy, where one can transmit a secret message securely without encrypting it by a prior key. Quantum dialogue (QD) is a process of two way secure and simultaneous communication using a single channel and quantum conference (Q.Conf) is a process of securely exchanging messages between three or more parties, using quantum resources. Deterministic secure quan- tum communication (DSQC) is another class of quantum secure communication protocol, to transmit secret message without any shared key, where at-least one classical bit is required to decrypt the secret message. In the practical scenario, an adversary can apply detector-side- channel attacks to get some non-negligible amount of information about the secret message. Measurement-device-independent (MDI) quantum protocols can remove this kind of detector- side-channel attack, by introducing an untrusted third party (UTP), who performs all the measurements in the protocol with imperfect measurement devices. For secure communica- tion, identity authentication is always important as it prevents an eavesdropper to impersonate a legitimate party. The celebrated Clauser, Horne, Shimony, and Holt (CHSH) game model helps to perform the security analysis of many two-player quantum protocols. In this thesis, we perform analysis of several existing QSDC and QD protocols, and also design some new efficient protocols. We present new approaches of QSDC, QD and DSQC protocols with user authentication, some of them are MDI protocols. We analyze the security of a QSDC protocol, an MDI-QSDC protocol, and an MDI-QD protocol. We improve the previous protocols and propose some modifications of the above protocols. We also present a Q.Conf protocol by generalizing the previous MDI-QD protocol and using the algorithm of the Q.Conf protocol, we propose a quantum multi-party computation protocol to calculate the XOR value of multiple secret numbers. Next, we generalize the CHSH game, and we demonstrate how to distinguish between dimensions two and three for some special form of maximally entangled states using the generalized version of the CHSH game.
Introduction -- Background -- Analysis and Design of QSDC Protocol -- A New Approach of QSDC Design using a Single Basis -- Analysis and Design of MDI-QSDC -- A New Approach of MDI-QSDC Design with User Authentication -- Analysis and Design of MDI Quantum Dialogue Protocols -- Analysis and Design of Quantum Conference Protocols -- Dimensionality Distinguisher -- Conclusion
Thesis (Ph.D.) - Indian Statistical Institute, 2022
Includes bibliography
Guided by Prof. Goutam Paul
Keywords: Computer Science; Communication System; Quantum Secure Communication System; Cryptology; Quantum Mechanics